Job satisfaction at workplace : a case of doctors in government hospital, Kuala Lumpur, Malaysia / Mohd Ramlan, M. A, Rugayah, H and Zarul Zafuan, M. D - M. A, Mohd Ramlan; H, Rugayah; M. D, Zarul Zafuan (Universiti Teknologi MARA, Shah Alam, 2014)
The purpose of this paper is to describe the results of a study on work satisfaction among doctors at a government hospital. This is a fundamental study using cross-sectional survey of 150 doctors (n=150) at University Malaya Medical Center (UMMC). Data was collected via questionnaires and the returned response was 100%. Although the working hours are long and grueling, the findings showed that 58% are satisfied with their work (M=4.34, SD=0.59) for the following reasons; adequate support from seniors, meaningful tasks, flexible work schedule and good career prospects. The hospital management should adjust their policy by tracking the doctors’ wellbeing and maintaining the positive factors in their environment to reduce turnover and attrition rates among doctors.